Assessment of Analgesic, Cytotoxic and Antioxidant activities of Vallaris solanacea (Roth) Kuntze (Stamford Journal of Pharmaceutical Sciences, 2011)
The ethanolic extract of leaves and stem of Vallaris solanacea (Roth) Kuntze (Family: Apocynaceae) was screened for its analgesic, cytotoxic and antioxidant activities. Phytochemical analysis of the extract indicated the presence of Reducing Sugar, Tannins, Saponins, Gums, Steroids, Alkaloids, and Glycosides. The ethanolic extract showed statistically significant analgesic activity (p